Parasites of urban coyotes - Chambers, Jackson (My University, 2017)
Interactions between coyotes (Canis latrans) and humans are an increasing problem, not only because of potential injuries from aggressive coyotes, but also because of potential transmission of zoonotic parasites and infections. Through the Edmonton Urban Coyote Project at the University of Alberta, seventeen coyotes were donated to MacEwan University where they were examined for internal parasites. As well, overall body condition of coyotes was assessed. This work provides data that illustrates how heavily parasitized the coyotes in the metropolitan Edmonton area are as well as data on parasite site-specificity and relationship between the number of parasites and splenic weight to body ratio in coyotes. Similar studies have been done throughout North America, namely Edmonton’s neighboring city to the south, Calgary, which had a much lower species richness than this study. This information will be useful in educating the general population on the dangers of urban coyotes and the importance of exercising caution when walking and cleaning up after pets.
Presented on April 24, 2017 at Student Research Day held at MacEwan University in Edmonton, Alberta.